2021
DOI: 10.1002/er.6362
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and optimization of thermosensitive hydrogels for inhibiting coal oxidation

Abstract: Currently, the prevention and control of coal spontaneous combustion (CSC) mainly depend on liquid or inert gas injection. In this study, the mixed sol solution was prepared with methylcellulose (MC), polyethylene glycol (PEG), and surfactant sodium dodecyl sulfate (SDS). It has the advantages of in-situ, nontoxicity, easy biodegradation, etc., and can retain a large amount of water by sol-gel transition. The effect of each component on the gel properties was analyzed by using central composite design (CCD) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…34 With the increase of treatment temperature, the band intensities at 2915 and 2850 cm À1 (CH 2 , CH 3 asymmetrical stretching vibration) decrease, apparently, compared with raw coal, which suggests that more soluble constituents were extracted at higher temperatures. 35 Due to dewatering of ZDC during thermal treatment, the band intensity of OH ranging from 3300 to 3700 cm À1 for all treated coals is considerably weak.…”
Section: Gas Release and Functional Group Changesmentioning
confidence: 95%
“…34 With the increase of treatment temperature, the band intensities at 2915 and 2850 cm À1 (CH 2 , CH 3 asymmetrical stretching vibration) decrease, apparently, compared with raw coal, which suggests that more soluble constituents were extracted at higher temperatures. 35 Due to dewatering of ZDC during thermal treatment, the band intensity of OH ranging from 3300 to 3700 cm À1 for all treated coals is considerably weak.…”
Section: Gas Release and Functional Group Changesmentioning
confidence: 95%
“…Cheng et al prepared a new type of smart gel for mining, which could effectively utilize corn stalks, contained expandable graphite that responded rapidly to temperature, and had good thermal stability and fire extinguishing properties . Guo et al physically cross-linked an MC-PEG-SDS ternary thermosensitive hydrogel, characterized its properties, and found that it could effectively suppress coal oxidation . Tsai et al prepared five coal spontaneous combustion inhibitors such as P­(NIPA-co-SA) thermosensitive hydrogel and compared their comprehensive properties by FTIR, TG, and other characterization methods .…”
Section: Introductionmentioning
confidence: 99%
“… 34 Therefore, it is insufficient to use noncoal reference samples in the experiments of low-rank coal, especially for high-moisture-content coal. 35 , 36 …”
Section: Introductionmentioning
confidence: 99%
“…The change of the structure will significantly change the spontaneous combustion characteristics of coal. With the decrease in the particle size, the moisture content, the heat of wetting release, and the risk of spontaneous combustion increase . Therefore, it is insufficient to use noncoal reference samples in the experiments of low-rank coal, especially for high-moisture-content coal. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation